Performativity And Body Politics: Negotiating Identity in Toni Morrison's Beloved - Wilujeng Asih Purwani (FKIP, Universitas Palangka Raya, 2026)
This study aims to explain the construction of gender identity in Toni Morrison's novel Beloved through Judith Butler's gender performativity theory. This novel tells the story of the traumatic experience of slavery that shapes racial identity as well as the social issues, power relations, and extreme violence depicted within it. This study explains how Sethe and other female characters in the novel Beloved construct and demonstrate their identities through concrete actions as a form of protest against slavery. Based on Judith Butler's performativity approach, identity is not understood through a fixed biological destiny but rather as a repetition of social practices and norms within society. In the novel Beloved, Black women are represented not as a fixed biological essence but as the result of the application of norms in society. In Beloved, the Black female body is depicted as a source of oppression and a space of resistance. The system of slavery in Beloved not only controls the physical body but also women's subjectivity. Sethe's actions in protecting her child in the novel can be read as an attempt to shake up hegemonic maternal norms. The results of this study indicate that Morrison portrays identity as a political construct and always in the process of becoming. The trauma depicted in the novel is a performative mechanism that shapes the characters' subjectivities. Thus, an analysis of gender performativity in Beloved cannot be separated from the intersectional issues of race, history, slavery, and patriarchal culture.